hUC-MSC extracellular vesicles protect against hypoxic-ischemic brain injury by promoting NLRP3 ubiquitination - Shanshan Xiao; Ying Lv; Xuejing Hou; Shuqiang Qu (Biomolecules & Biomedicine)
Hypoxic-ischemic brain injury (HIBD) is a major cause of neonatal mortality and long-term neurological deficits, with limited treatment options. Extracellular vesicles (EVs) from human umbilical cord mesenchymal stem cells (hUC-MSC-EVs) have shown promise in neuroprotection, but the mechanisms remain unclear. This study explores how hUC-MSC-EVs protect neonatal rats from HIBD. hUC-MSC-EVs were isolated, characterized, and administered to neonatal rats subjected to HIBD. Behavioral reflexes and brain infarction were assessed, along with cellular and molecular analyses of hippocampal tissue. An in vitro oxygen–glucose deprivation/reoxygenation (OGD/R) model was used to simulate ischemic conditions in rat primary microglia. Results demonstrated that hUC-MSC-EVs significantly improved neurological outcomes, reduced brain infarction, and decreased microglial activation and pyroptosis. These effects were linked to the inhibition of NLRP3 inflammasome activation and enhanced ubiquitination via the protein kinase A (PKA) pathway. Blocking PKA partially reversed these protective effects. Here we highlight that hUC-MSC-EVs provide neuroprotection by regulating the NLRP3 inflammasome, offering a potential therapeutic strategy for HIBD. These findings expand the understanding of EV-mediated neuroprotection and suggest broader applications for ischemia-related conditions, with potential for clinical translation.